DEVELOPMENT OF SIMPA INTERACTIVE MULTIMEDIA BASED ON LOCAL WISDOM IN PANCASILA EDUCATION FOR FOURTH GRADE ELEMENTARY SCHOOL - Dewi, Ni Luh Putu Putri Noviani; Dharma, I Made Aditya; Dewi, Made Sri Astika (STKIP Citra Bakti, 2026)
The limited use of interactive media in elementary schools, particularly in the subject of Pancasila Education on the topic of the meaning of Pancasila principles and the application of its values, serves as the background of this study. This study aims to develop an interactive multimedia tool, “SIMPA” (Sila Makna Pancasila), based on local wisdom that is suitable for use by fourth-grade elementary school students. The method employed in this study is Research and Development (R&D) using the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 25 fourth-grade students of SD Negeri 1 Lelateng and one classroom teacher. Data were collected through observation, interviews, documentation, and questionnaires, and were analyzed using both qualitative and quantitative approaches. The results indicate that the “SIMPA” interactive multimedia has a very high level of validity. This is evidenced by the validation results from media experts, which reached 96.4%, and from material experts, which reached 90.67%, both categorized as “very valid.” Based on these findings, the “SIMPA” interactive multimedia based on local wisdom is considered suitable for implementation in Pancasila Education learning in elementary schools. In conclusion, the “SIMPA” interactive multimedia is capable of supporting a more effective, engaging, and innovative learning process. Therefore, it is recommended that this media be utilized more widely in educational practices and further developed for different materials and educational levels.